The ideology of neoconservatism in the classification of international relations - Turaev, Abrar (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article describes the role of the US ideology of neoconservatism in the system of international relations, approaches tonational interests, the methodological basis of modern neoconservative theories